As relações jugoslavo-portuguesas (1941-1974) - Jorge Santos Carvalho (Documentos, 2012)
This volume contains documents from archives in Belgrade covering topics and events from Portuguese history and Portuguese-Yugoslav relations between 1941 and 1974. This documentation gives an overview of those years, divided into two distinct periods divided by an 'interregnum' (1949-60), when diplomatic and party relations were suspended (in April 1948 the Yugoslav delegation was closed and relations were cut between the Portuguese and Yugoslav Communist parties).ALT_QUEBRA_LINHAUntil the middle of 1945, the legation's main activities were concerned with monitoring the war and its consequences. Then, connections were forged and support developed for the Portuguese anti-fascist opposition (MUNAF, MUD e PCP) through diplomats of a Yugoslavia that was very different to what it had been in 1941. After the interregnum (1950s), these contacts were resumed (FPLN, PCP and ASP/PSP) and were maintained, with greater or lesser intensity, until 1974. Similarly, in this period, there was Yugoslav support for the liberation movements in the Portuguese colonies (PAIGC, MPLA and FRELIMO).